Cost Effective Negative Plenum Cleanroom for Microelectronic Engineering undergraduate - Uda, Hashim; Zul Azhar, Zahid Jamal; Mohammad Nuzaihan, Md Nor; Nur Hamidah, Abdul Halim (Kolej Universiti Kejuruteraan Utara Malaysia, 2008)
Link to publisher's homepage at http://jere.unimap.edu.my